PERANAN WAKAF TUNAI UNTUK PENDIDIKAN: KAJIAN KES DI BANK MUAMALAT MALAYSIA BERHAD : The Role of Cash Waqf for Education: The Case Study of Bank Muamalat Malaysia Berhad - Mahyudin, Mohd Izuwan; Ab Rahman, Asmak (Jurnal Syariah, 2023)
It is incumbent upon the government to undertake the provision of educational amenities, a duty that underscores its responsibilities. However, Malaysia's educational framework faces an escalating challenge, primarily stemming from the mounting costs associated with facilitating educational infrastructure. To ensure the uninterrupted delivery of quality education, the participation of waqf-developing institutions becomes pivotal in aiding the government, including private entities such as financial institutions. This study extensively examines the deployment of cash waqf funds, particularly those executed by banking institutions, using Bank Muamalat Malaysia Berhad (BMMB) as a reference. This bank has undertaken pioneering waqf initiatives in collaboration with the State Islamic Religious Council to advance education. This study employs a qualitative approach, entailing data collection from diverse pertinent documents, coupled with interviews involving three key personnel from Bank Muamalat Malaysia Berhad (BMMB). The study's findings underscore the Bank's tangible potential to significantly contribute to the advancement of waqf in Malaysia by means of cash waqf initiatives. Bank Muamalat Malaysia Berhad (BMMB) has notably undertaken multiple contributions within the sphere of educational waqf. These contributions encompass diverse initiatives, ranging from the establishment of educational centres to the provisioning of essential educational resources and facilities, even extending to the provision of waqf-based vehicles. The study reveals a considerable potential for the enhancement of educational waqf by engaging corporate entities, notably banking institutions.